Optimation of sodium citric and fumaric acid as acid sources in effervescent granule of Curcuma xanthorrhiza Roxb. extract by wet granulation - Lestari, A. Budi Susiana; Natalia, Lisa (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2007)
Temulawak (Curcuma xanthorrhiza Roxb.) is one of natural drugs spread throughout Indonesia. Based on researches and experiences, temulawak has been proven to cure some diseases. This research applied combination of sodium citrate and fumaric acid as excipients to produce effervescent granule with certain physical characteristics.The aims of this research were to observe dominant factor and the interaction effect between sodium citrate and fumaric acid, to find out the optimal area of sodium citrate and fumaric acid mix to produce effercescent granule which fulfill the granule requirements. The research used factorial design method with two factors and two levels.The physical characteristics of effervescent granule, evaluated were moisture content, flow rate and time to disintegrate and dissolve. The results showed that sodium citrate dominant in moisture content and time, whereas fumaric acid dominant in granule flow properties. Under research circumstances, contour plot super imposed fail to show the optimum area for moisture content, flow rate and time to disintegrate and dissolve of effervescent granule can’t be obtain from contour plot super imposed under the research condition.Key words : Curcuma xanthorrhiza Roxb., sodium citric,fumaric acid, factorial design